PENGGUNAAN BAHAN ALAM UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V MEMBUAT CETAK/ SENI GRAFIS DI SEKOLAH DASAR - Guslinda Guslinda; Gustimal Witri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The reasearcher found that there was low students’ creativity in learning painting arts, especially on the graphicarts. The purpose of this research was to improve on year Vc students’ creativity in making graphic arts by usingthe natural material at Public Elementary School (SDN) 112 Pekanbaru. This research used the classroomaction research and it had two cycles for each process. Based on the data analysis for the first cycle, the resultindicated that there were 2 students got (5%) for high creative category, 16 students (40%) for an adequatecreative category, and there were 22 students’ (55%) on the level of low creative category. In other words, theaverage of the first cycle result was 63,97%. Furthermore, after using the natural material at the end of cycle I,there was the improvement on each category. They are 17,5% (7 students) for high creativity, 82,5% (33students) for an adequate creativity. It showed that there was 69,06% for its cyclical average. Moreover, at theend of cycle II, the students’ creativity improved significantly into 81,8% in comparing with cycle I. That is, 12students (30%) got high category for the creativity, 16 students (40%) got creative category, and 12 students(30%) were on the level of an adequate creative category. Based on the data result above, it can be concludedthat the use of natural material can improve year Vc students’ creativity in making graphic arts at PublicElementary School 112 Pekanbaru.